New records of Leptotyphlops borrichianus Degerbøl, 1923 in northwestern Patagonia - Perez, Cristian Hernan Fulvio (2010)
Leptotyphlopid snakes are rare in southern Argentina, but as result of several field trips carried out in the last years we collected a few specimens of Leptotyphlos borrichianus. Some of them represent new localities for the species in the region. In addition, we comment on previous records of Leptotyphlos borrichianus in northwestern Patagonia.